Developing teachers’ professional performance based on dual intelligence: a mediation perspective - Widodo, Widodo; Sumadyo, Bambang; Suparman, Heru; Tjitrosumarto, Sumaryati (Institute of Advanced Engineering and Science, 2024)
Teacher professional performance is crucial for schools to improve students’ academic performance and success. However, research on this issue still needs to be completed, including the factors influencing it. Therefore, this study focuses on investigating the role of interpersonal communication skills (ICS) in mediating cultural intelligence (CI) and emotional intelligence (EI) affect teachers’ professional performance. The participants are 455 Indonesian teachers selected by accidental sampling from three provinces in Indonesia. Data was collected by distributing Likert scale questionnaires and analyzed using structural equation modeling (SEM) performed by LisRel 8.80. All hypotheses were supported (significant). It means CI, EI, and ICS are related to teachers’ professional performance; CI and EI link to teachers’ ICS; and ICS mediates CI and EI affect teachers’ professional performance. This evidence promotes a new model of CI and EI affecting teachers’ professional performance via ICS. It provides a theoretical contribution, and practical implication requires critical discussion among researchers, scientists, and practitioners.